PEMBERDAYAAN EKONOMI MASYARAKAT MELALUI PENGEMBANGAN UMKM LOKAL DI KECAMATAN MANTIKULORE KOTA PALU - Rukhayati; Rahmi, Risma; Heriani; Putri, Yuliana; Dewi Febri Anawati (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to improve the independence and economic welfare of the community through the development of local Micro, Small, and Medium Enterprises (MSMEs) in Mantikulore District, Palu City. The main problems faced by MSME partners include limitations in business management, lack of access to digital marketing technology, and low quality product packaging, which limits competitiveness. Community service activities are carried out through business management mentoring, digital-based marketing training, and innovation in product packaging. The methods used include outreach, workshops, technical guidance, and continuous monitoring and evaluation. The results of the activities show an increase in knowledge and skills of MSME actors, improved product quality, and expanded market access both offline and online. Thus, this program is expected to strengthen the capacity of local MSMEs, increase competitiveness, and encourage economic growth in the Mantikulore District, Palu City.